Newton’s Method for the Matrix Nonsingular Square Root - Chun-Mei Li; Shu-Qian Shen (Journal of Applied Mathematics)
Two new algorithms are proposed to compute the nonsingular square root of a matrix A. Convergence theorems and stability analysis for these new algorithms are given. Numerical results show that these new algorithms are feasible and effective.